Problematic aspects of the doctor-patient relationship in international human rights law - Scalabrino Spadea, Michelangela (Medicina e Morale, 1986)
Numerous precepts of international law can and must be taken into consideration even before domestic rules when seeking solutions to the many problematic legal cases that arise in the professional doctor-patient relationship. In fact, international law also constitutes in this matter a complex of provisions that are often more articulated than state regulations, and therefore can well serve as a priority source of positive regulations or exegetical indications. Moreover, it ensures identical rules for identical cases, provided that the State has provided for the adaptation of its own legal system.